An analytical model to predict strain-hardening behaviour and twin volume fraction in a profoundly twinning magnesium alloy. (August 2019) - Sahoo, Sudeep K.; Toth, Laszlo S.; Biswas, Somjeet
Abstract: An analytical model is presented that can successfully predict the strain hardening behaviour as well as the variations in twin volume fraction in polycrystalline Magnesium alloy Mg-3Al-0.3Mn that twins profoundly during deformation. The model is composed of three basic elements: (i) Twin fraction prediction, based on crystal plasticity elements, (ii) a two-phase composite model composed of the matrix and the twins by adopting the "Iso-work" hypothesis, (iii) a strain hardening approach inspired from a crystal plasticity model. The experiments include uniaxial compression tests for two different cases at ambient temperature. The microstructures were characterized at various strains up to fracture using the Electron Back-Scattered Diffraction technique in a FEG-SEM. The microstructural investigation revealed the formation of a lamellar structure of alternated layers of matrix and 10 1 ¯ 2 〈 10 1 ¯ 1 ¯ 〉 -extension twin domains. With progressive deformation, the twins broadened and consumed the entire microstructure prior to fracture. The model could accurately reproduce the experimental twin-induced sigmoidal shaped flow curve together with the twin volume fraction evolution. Graphical abstract: Image 1 Highlights: A new analytical model is presented for strain hardening and twinning in Mg. The twinning fraction is given by a single-parameter analytical function. The matrix-twin composite uses the uniform work hypothesis. The strain hardening is based on a simplified crystal plasticity law. It has been shown that both texture-hardening and dislocation hardening occurs in Mg.